The Potential of Virtual Reality for the Investigation of Awe - Chirico, Alice; Yaden, David B.; Riva, Giuseppe; Gaggioli, Andrea (Frontiers in Psychology, 2016)
The emotion of awe is characterized by the perception of vastness and a need for accommodation, which can include a positive and/or negative valence. While a number of studies have successfully manipulated this emotion, the issue of how to elicit particularly intense awe experiences in laboratory settings remains. We suggest that virtual reality (VR) is a particularly effective mood induction tool for eliciting awe. VR provides three key assets for improving awe. First, VR provides users with immersive and ecological yet controlled environments that can elicit a sense of “presence,” the subjective experience of “being there” in a simulated reality. Further, VR can be used to generate complex, vast stimuli, which can target specific theoretical facets of awe. Finally, VR allows for convenient tracking of participants’ behaviour and physiological responses, allowing for more integrated assessment of emotional experience. We discussed the potential and challenges of the proposed approach with an emphasis on VR’s capacity to raise the signal of reactions to emotions such as awe in laboratory settings.